Rethinking human–technology relations: exploring the sociopolitical dimensions of invasive brain stimulation - Amanda van Beinum (Humanities & Social Sciences Communications)
Abstract Approaching the meeting of human and technology as a relation involves recognition of the plethora of already existing connections and associations between humans and non-human artifacts, as well as how connections grow and change over time. When connection between human and technology is a relation, it has no clear beginning or end point, no before or after. Instead, there are variations and modifications in the strength and quality of the relation. This paper argues that adequate conceptualization of human-technology contact as an ongoing relationship rather than a discrete interaction requires a broadening of scope beyond individual human users and technological devices. Using the application of deep brain stimulation (DBS) for cases of mental illness as an example, the paper explores how a relational approach to analysis brings forward important ethical and social issues warranting further scrutiny. Historical narratives of device development interpreted through theoretical perspectives of critical disability studies facilitate consideration of how social preferences for “normality” shape user perceptions of safety and effectiveness of yet clinically unproven treatments. Exploring experiences of embodiment through critical disabilities and posthuman critiques foregrounds how vulnerability and resilience are constructed through relational networks of interdependence, themselves novel forms of care. Finally, application of interdisciplinary perspectives to the study of human-technology relations opens up new analytic approaches for studying questions of embodiment, agency, and control precipitated through the development, surgical insertion, and experimental use of technology. Expanding beyond human-technology interactions to analyze the complexity of ongoing relations facilitates an opening-up of discussions around implanted technologies like DBS and invites further investigation of how novel human-technology pairings have the potential to effect social and political change.